2016
DOI: 10.14202/vetworld.2016.192-198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding different levels of Azolla pinnata on blood biochemicals, hematology and immunocompetence traits of Chabro chicken

Abstract: Aim: The present study was conducted to see the effect of feeding different levels of Azolla meal on blood biochemicals, hematology and immunocompetence traits of Chabro chicken. Materials and Methods:The study was conducted on 160 Chabro chicks, which were randomly divided into four treatment groups each with four replicates of 10 birds. The first treatment (T 1 ) served as a control in which basal diets was offered without Azolla supplementation while in T 2 , T 3 , and T 4 groups, basal diet was replaced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
3
17
1
Order By: Relevance
“…In addition, the utilization of SML in Kampong chickens significantly reduces low density lipoprotein (LDL) and increases high density lipoprotein (HDL). This result is in line with the results reported by Al-Rekabi et al (2020), Aderemi et al (2018), and Mishra et al (2016) in which the substitution of the aquatic plant instead of soybean meal can lead to the improved some of the biochemical blood traits for chicken. Further research is necessary to determine the quality of Kampong Chicken meat by incorporating SML leaf in the diet.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the utilization of SML in Kampong chickens significantly reduces low density lipoprotein (LDL) and increases high density lipoprotein (HDL). This result is in line with the results reported by Al-Rekabi et al (2020), Aderemi et al (2018), and Mishra et al (2016) in which the substitution of the aquatic plant instead of soybean meal can lead to the improved some of the biochemical blood traits for chicken. Further research is necessary to determine the quality of Kampong Chicken meat by incorporating SML leaf in the diet.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no significant differences were observed among the experimental groups of total serum protein (g/dl), albumin, globulin, AST and ALT as presented in Table ( 4) and falls within the normal range which was reported by Özkan et al (2012). These results have support from a study by Mishra et al (2016) who found similar values and within the normal values of blood cholesterol, total protein, albumin, and triglycerides in all broiler chicken groups fed diets replaced with 5%, 7.5% and 10% levels Azolla meal. They also reported that liver enzymes in blood was found similar in all treatment groups.…”
Section: Serum Biochemicalsupporting
confidence: 87%
“…Diabetic rats fed on azollacaroliniana by different percentages showed significant decreases in serum AST,ALT and ALP compared with the rats injected by alloxan. The percent of decreases as compared to control (+) group were -9.009%, -11.89% and -16.78% for AST and -23.66%, -36.16% and -40.17% for ALT and -16.04%, -29.30% and -50.69% for ALP for Azollacaroliniana by 1, 2.5, 5% respectively, considering serum AST,ALT and ALP, Azollacaroliniana 5% group recorded that the best treatment was observed for when compared to control (-) group.This results disagree with (Mishra et al, 2016), they found that feeding chicken with different levels of Azolla increased serum AST and significantly decreasing serum ALP but didn't show any significantly differences concerning serum ALT comparing control (-) group.…”
Section: Effect Of Azolla Algae On Liver Functions (Ast Alt and Alp) Of Diabetic Ratscontrasting
confidence: 65%